2014
DOI: 10.1042/cs20140481
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated telomere attrition of lymphocytesin vivois co-ordinated with changes in telomerase activity, composition of lymphocyte subsets and health conditions

Abstract: Telomeres are essential in maintaining chromosome integrity and in controlling cellular replication. Attrition of telomere length in peripheral blood mononuclear cells (PBMCs) with age is well documented from cross-sectional studies. But the actual in vivo changes in telomere lengths and its relationship with the contributing factors within the individuals with age have not been fully addressed. In the present paper, we report a longitudinal analysis of telomere length in the PBMCs, lymphocytes and monocytes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 43 publications
4
97
2
2
Order By: Relevance
“…Consistent with their origin from infant thymus, thymic Tregs have significantly longer telomere length than adult blood Tregs. Telomere shortening is one of the molecular hallmarks of aging (50)(51)(52). Vukmanovic-Stejic et al showed that rapid peripheral turnover is responsible for the maintenance of human Tregs during aging and is associated with critically short telomeres, low telomerase activity, and higher susceptibility to apoptosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their origin from infant thymus, thymic Tregs have significantly longer telomere length than adult blood Tregs. Telomere shortening is one of the molecular hallmarks of aging (50)(51)(52). Vukmanovic-Stejic et al showed that rapid peripheral turnover is responsible for the maintenance of human Tregs during aging and is associated with critically short telomeres, low telomerase activity, and higher susceptibility to apoptosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also did not measure telomerase activity, which could have an impact on the current findings. It is known that telomerase influences the rate of change in TL of peripheral blood mononuclear cells (Lin et al, 2015).Additionally, the cross-sectional design does not allow assessment of within-individual changes in TL over the lifespan. This approach is only able to estimate how the cellular aging processes may proceed based on measurement of individuals with a range of ages and exposures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Changes observed in the immune system of RA patients are similar to those in the elderly, leading ultimately to breach of self-tolerance. Just like in older individuals, telomere shortening in the lymphocytes [19], T-cell aging and emergence of CD28-cells are seen in RA patients [13]. But whether these changes suggesting immunosenescence are a cause or a consequence of RA is still unclear.…”
Section: Rheumatoid Arthritis In the Elderlymentioning
confidence: 99%
“…Similarly in this cohort, adverse events were not different between age groups. 19 Long-term analyses of the clinical trials and within real-life cohorts indicate that the withdrawal rate for this drug is relative low e.g just over 30% after two years in a large reallife cohort [89] and mainly occurring during the first two courses in around one-third of patients, irrespective of age (even in the very elderly, ≥ 75 years) [91]. Comparisons of drug survival among different biological agents is not easy as the administration interval may play a role in the patient's or physician's decision to stop a given treatment, but also in the recording and analysis of drug survival data.…”
Section: Rituximabmentioning
confidence: 99%